2016
DOI: 10.1073/pnas.1523981113
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for oligomerization and glycosaminoglycan binding of CCL5 and CCL3

Abstract: CC chemokine ligand 5 (CCL5) and CCL3 are critical for immune surveillance and inflammation. Consequently, they are linked to the pathogenesis of many inflammatory conditions and are therapeutic targets. Oligomerization and glycosaminoglycan (GAG) binding of CCL5 and CCL3 are vital for the functions of these chemokines. Our structural and biophysical analyses of human CCL5 reveal that CCL5 oligomerization is a polymerization process in which CCL5 forms rod-shaped, double-helical oligomers. This CCL5 structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 55 publications
0
83
0
Order By: Relevance
“…The 30s loop was shown to establish only complementary GAG-interactions in CCL5 (56) and it was proposed to be important for the CX3CL1-GAG interaction; however, this was not demonstrated experimentally (57). On the other hand, the 50s loop has been shown to be critical for the GAG-binding of members of other chemokines subgroups and of CC chemokine oligomers (58,59). Furthermore, we found that the N-terminus of the rm131 chemokine domain plays a more limited role in GAG-binding than it does for other CC chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…The 30s loop was shown to establish only complementary GAG-interactions in CCL5 (56) and it was proposed to be important for the CX3CL1-GAG interaction; however, this was not demonstrated experimentally (57). On the other hand, the 50s loop has been shown to be critical for the GAG-binding of members of other chemokines subgroups and of CC chemokine oligomers (58,59). Furthermore, we found that the N-terminus of the rm131 chemokine domain plays a more limited role in GAG-binding than it does for other CC chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…Some chemokines form higher order oligomers (Fig. 1e) (74), many of which utilize both CC and CXC dimerization interfaces (72, 89). …”
Section: Chemokines: Structure and Biologymentioning
confidence: 99%
“…In that case, to preserve local CCL3 gradient around migrating GC B cell, secreted CCL3 would have to be rapidly internalized and removed by other cells within GCs. Alternatively to the first model, CCL3 chemokine secreted by GC B cells could be transiently immobilized on the surface of selected GC B cells in association with chemokine-binding glycosaminoglycans (Liang, Triandafillou et al 2016) and may serve to stabilize very transient probing interactions of GC B cells with Tfr cells that are beyond the resolution capabilities of intravital 2P microscopy. Both of these models can lead to decreased efficiency in productive sampling of CCL3 KO B cells by Tfr cells.…”
Section: Discussionmentioning
confidence: 99%